Gestão ambiental urbana no poder público municipal de Aracaju: desafios e estratégias - Silva, Edson Oliveira da (2017)
The present study is based on the year 2008, when the city of Aracaju was considered the capital of quality of life. In order to understand that there is an intrinsic relationship between environmental management and quality of life, the following question was raised: what are the challenges and strategies of urban environmental management in the municipal public power of Aracaju, from 2008 to 2016? It is important to note that, in 2013, the Municipal Secretariat of the Environment (Sema) was created in the Sergipe capital with the purpose of promoting environmental management in the city of Aracaju. With this, strategies were established to meet the challenges arising from environmental liabilities. In this context, the study on screen has as general objective to analyze the challenges and strategies of environmental management in the municipal administration of Aracaju in the aforementioned period. For this, during the investigation, the "Case Study" methodology was used as methodology, where bibliographical and documentary research was used, with emphasis on the application of the technique of content analysis in the information collected in the official website of the Municipality of Aracaju (WFP) and Sema's "Management Reports". This technique was also applied to the content of the interviews conducted with those who exercised strategic functions in the municipal environmental management of the Sergipe capital. The present work contributes to the interdisciplinary analysis and cooperates to provide an overview of the challenges and strategies of environmental management in Aracaju, that is, it is a document that serves as a roadmap for the promotion of public policies in the environmental area. As a result, it can be seen that with Sema there was a significant increase in the fulfillment of environmental demands. Finally, throughout the research the importance of environmental licensing, inspection and environmental education for the promotion of environmental quality was verified.